Sleeve grouting material for steel bar connection and sleeve grouting method
By using a combination of silicate antifreeze and polycarboxylic acid antifreeze in the sleeve grouting material and adding self-healing microcapsules, the problem of degradation of steel bar connection quality in low temperature environments is solved, and high strength, durability and self-healing effects are achieved.
Patent Information
- Application Number
- CN202411969366.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-18
AI Technical Summary
During construction in low temperature environments, the solidification time of traditional sleeve grouting materials is extended and the strength is reduced, which affects the quality of the steel bar connection.
A sleeve grouting material for steel bar connection is developed, which contains a combination of antifreeze containing silicate antifreeze and polycarboxylic acid antifreeze. The amount of antifreeze is accurately controlled according to the ambient temperature, and self-healing microcapsules are added to improve durability.
Maintain good fluidity and solidification performance in low temperature environments, improve the strength and durability of steel bar connections, and achieve self-healing when the temperature rises, significantly improving the overall performance of the structure.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials and relates to a sleeve grouting material for connecting steel bars and a sleeve grouting method. Background Art
[0002] In construction projects, steel bar connection is one of the key links in structural safety. Traditional steel bar connection methods often have problems such as difficult construction and insufficient connection strength. In recent years, sleeve grouting connection technology has been widely used due to its advantages such as simple construction and reliable connection. However, when constructed under cold conditions such as low temperature environments, the setting time of the grouting material is prolonged and the strength is reduced, which seriously affects the connection quality. Therefore, it is particularly important to develop a sleeve grouting material with excellent frost resistance and construction performance. Summary of the invention
[0003] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0004] Another object of the present invention is to provide a sleeve grouting material for steel bar connection. The grouting material of the present invention has excellent frost resistance and is suitable for steel bar connection operations in various low temperature environments.
[0005] To this end, the technical solution provided by the present invention is:
[0006] A sleeve grouting material for steel bar connection, comprising the following components in parts by weight:
[0007] 200-300 parts of cement, 90-270 parts of admixture, and 160-175 parts of antifreeze and water, wherein the antifreeze comprises a silicate antifreeze and a polycarboxylic acid antifreeze in a mass ratio of 10:1, wherein when used at a temperature of 0 to -4°C, the amount of the antifreeze accounts for 0.8% to 2% of the total weight of the cement and the admixture; when used at a temperature of -4 to -10°C, the amount of the antifreeze accounts for 1.8% to 3% of the total weight of the cement and the admixture; when used at a temperature below -10°C, the amount of the antifreeze accounts for 3% to 8% of the total weight of the cement and the admixture.
[0008] Preferably, the sleeve grouting material for steel bar connection also includes the following components in parts by weight: 6 to 9 parts of self-repairing microcapsules, wherein the core of the self-repairing microcapsules includes alkaliphilic Bacillus spores and calcium lactate in a mass ratio of 2:1 to 5, the capsule wall of the self-repairing microcapsule is magnesium phosphate cement, and the mass ratio of the capsule wall to the capsule core is 2 to 10:1.
[0009] Preferably, the sleeve grouting material for steel bar connection further comprises the following components in parts by weight: 1 to 5 parts of a water reducing agent and 0.1 to 1 part of a defoaming agent.
[0010] Preferably, the sleeve grouting material for steel bar connection further comprises the following components in parts by weight: xanthan gum and / or sepiolite, wherein the amount of the xanthan gum and / or sepiolite accounts for 0.05% to 0.2% of the total weight of the cement and admixtures.
[0011] Preferably, the sleeve grouting material for steel bar connection further comprises the following components in parts by weight: 0.1 to 1.6 parts of plastic expansion agent and 7 to 8.4 parts of calcium oxide expansion agent.
[0012] Preferably, the sleeve grouting material for steel bar connection further comprises the following components in parts by weight: 90-120 parts of sand and 80-100 parts of stone.
[0013] The sleeve grouting method based on the sleeve grouting material for steel bar connection comprises the following steps:
[0014] Get the sleeve grouting environment temperature;
[0015] Inserting the steel bars into the prefabricated sleeves;
[0016] According to weight proportions, 200-300 parts of cement, 90-270 parts of admixtures, and 160-175 parts of antifreeze and water are taken. Antifreeze is taken according to the ambient temperature of sleeve grouting. The antifreeze includes silicate antifreeze and polycarboxylic acid antifreeze in a mass ratio of 10:1. When used at a temperature of 0 to -4°C, the amount of the antifreeze accounts for 0.8% to 2% of the total weight of the cement and admixtures. When used at a temperature of -4 to -10°C, the amount of the antifreeze accounts for 1.8% to 3% of the total weight of the cement and admixtures. When used at a temperature below -10°C, the amount of the antifreeze accounts for 3% to 8% of the total weight of the cement and admixtures. Part of the water is mixed with the antifreeze, and after the remaining water is mixed with the cement and admixtures, a mixture of part of the water and the antifreeze is added thereto and mixed evenly to obtain a grouting material.
[0017] The grouting material is poured into the sleeve to complete the grouting.
[0018] Preferably, the sleeve grouting method further comprises the following steps:
[0019] Take 90-120 parts of sand and 80-100 parts of stone and add them to the mixture of cement, admixture and remaining water and mix well;
[0020] Take 0.1-1.6 parts of plastic expansion agent, 7-8.4 parts of calcium oxide expansion agent, 1-5 parts of water reducer, 0.1-1 part of defoamer, xanthan gum and / or sepiolite, add them to part of water and antifreeze and mix them, then add them to the mixture of cement, admixture, sand, stone and remaining water and mix them to obtain the grouting material, wherein the amount of xanthan gum and / or sepiolite accounts for 0.05% to 0.2% of the total weight of the cement and admixture.
[0021] Preferably, the sleeve grouting method further comprises the following steps:
[0022] Alkaliphilic Bacillus spores and calcium lactate are mixed in a mass ratio of 2:1-5 under vacuum conditions to obtain a capsule core material, the capsule core material is crushed into micrometers, magnesium phosphate cement is used as a capsule wall, the capsule wall material is wrapped around the micrometer-sized capsule core material, and the self-healing microcapsules are obtained by drying the pellets;
[0023] Take 6 to 9 parts of the self-repairing microcapsules, add them into the grouting material and mix them evenly, and then pour them into the sleeve.
[0024] The present invention at least includes the following beneficial effects:.
[0025] 1) Excellent antifreeze performance: The present invention can accurately control the dosage and ratio of the antifreeze agent, so that the grouting material can maintain good fluidity and solidification performance in different low temperature environments;
[0026] 2) Good construction performance: The addition of water reducing agent and defoaming agent and the precise proportion of each component make the grouting material have good fluidity and easy construction;
[0027] 3) High strength and durability: The addition of sand, stone, plastic expansion agent, calcium oxide expansion agent and other components further improves the strength and durability of the grouting material.
[0028] 4) Self-repairing ability: The addition of the self-repairing microcapsules of the present invention enables the grouting material to automatically repair itself when microcracks appear and the temperature rises to an appropriate range (5°C to 45°C), thereby improving the durability of the structure;
[0029] In summary, the sleeve grouting material for steel bar connection and the preparation method thereof of the present invention have broad application prospects and significant social and economic benefits.
[0030] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0032] It should be understood that terms such as “having”, “including” and “comprising” used herein do not specify the existence or addition of one or more other elements or combinations thereof.
[0033] The present invention provides a sleeve grouting material for connecting steel bars, comprising the following components in parts by weight:
[0034] 200-300 parts of cement, 90-270 parts of admixture, 160-175 parts of antifreeze and water, wherein the antifreeze comprises silicate antifreeze and polycarboxylic acid antifreeze in a mass ratio of 10:1, wherein when used at a temperature of 0--4°C, the amount of the antifreeze accounts for 0.8%-2% of the total weight of the cement and admixture, when used at a temperature of -4--10°C, the amount of the antifreeze accounts for 1.8%-3% of the total weight of the cement and admixture, and when used at a temperature below -10°C, the amount of the antifreeze accounts for 3%-8% of the total weight of the cement and admixture. Preferably, the admixture is one or more of bentonite, zeolite powder, fly ash or silica fume, and 2%-5% of nano calcium carbonate is added to the admixture, which can significantly improve the strength and density of the grouting material, and at the same time improve its impermeability and durability. Preferably, the cement is silicate cement. More preferably, the cement is selected from silicate cement with strength grade 52.5R and above.
[0035] In the present invention, cement is used as the main cementitious material of the grouting material to provide strength support; admixtures are used to adjust the performance of the grouting material, improve workability, increase strength, etc.; by accurately controlling the amount of antifreeze, the grouting material can maintain good fluidity and solidification properties in different low temperature environments. Specifically, when the ambient temperature is 0 to -4°C, the amount of antifreeze accounts for 0.8% to 2% of the total weight of cement and admixtures; when the ambient temperature is -4 to -10°C, the amount of antifreeze accounts for 1.8% to 3% of the total weight of cement and admixtures; when the ambient temperature is lower than -10°C, the amount of antifreeze accounts for 3% to 8% of the total weight of cement and admixtures. The grouting material of the present invention has excellent frost resistance and is suitable for steel bar connection operations in various low temperature environments.
[0036] In some embodiments of the present invention, the following components are preferably included in weight: 1 to 5 parts of water reducing agent and 0.1 to 1 part of defoaming agent. More preferably, the water reducing agent is a polycarboxylic acid water reducing agent. The defoaming agent is an ether defoaming agent or a silicone defoaming agent. The fluidity of the grouting material is improved and the generation of bubbles is reduced, further improving the construction performance and strength.
[0037] In some schemes of the present invention, preferably, the following components are also included in weight proportions: xanthan gum and / or sepiolite, the amount of xanthan gum and / or sepiolite accounting for 0.05% to 0.2% of the total weight of the cement and admixtures, so as to enhance the water retention and crack resistance of the grouting material.
[0038] In some embodiments of the present invention, the following components are preferably included in weight: 0.1-1.6 parts of plastic expansion agent and 7-8.4 parts of calcium oxide expansion agent, so as to compensate for the volume shrinkage of the grouting material during the solidification process and improve the tightness and durability of the connection part.
[0039] In some embodiments of the present invention, the following components are preferably included by weight: 90-120 parts of sand and 80-100 parts of stone. More preferably, the sand is machine-made sand with a fineness modulus of 0.7-1.5, and the stone is 5-20 mm continuously graded crushed stone. This further improves the strength and durability of the grouting material.
[0040] In the above scheme, as a preference, the following components in parts by weight are also included: 6 to 9 parts of self-repairing microcapsules, wherein the capsule core of the self-repairing microcapsules includes alkaliphilic Bacillus spores and calcium lactate in a mass ratio of 2:1 to 5, and the capsule wall of the self-repairing microcapsules is magnesium phosphate cement, and the mass ratio of the capsule wall to the capsule core is 2 to 10:1. When microcracks appear in the grouting material, after water enters the cracks, when the temperature rises to a suitable range (5°C to 45°C), the alkaliphilic Bacillus spores in the capsule core germinate under suitable conditions and produce minerals such as calcium carbonate, which work together with calcium lactate to fill the cracks and achieve self-repair. The mass ratio of the capsule wall to the capsule core is 2 to 10:1 to ensure the stability and effectiveness of the microcapsules. In this way, when the temperature gradually rises, the self-repairing microgel can play the self-repairing function of concrete.
[0041] The sleeve grouting method based on the sleeve grouting material for steel bar connection comprises the following steps:
[0042] Get the sleeve grouting environment temperature;
[0043] Inserting the steel bars into the prefabricated sleeves;
[0044] According to weight proportions, 200-300 parts of cement, 90-270 parts of admixtures, and 160-175 parts of antifreeze and water are taken. Antifreeze is taken according to the ambient temperature of sleeve grouting. The antifreeze includes silicate antifreeze and polycarboxylic acid antifreeze in a mass ratio of 10:1. When used at a temperature of 0 to -4°C, the amount of the antifreeze accounts for 0.8% to 2% of the total weight of the cement and admixtures. When used at a temperature of -4 to -10°C, the amount of the antifreeze accounts for 1.8% to 3% of the total weight of the cement and admixtures. When used at a temperature below -10°C, the amount of the antifreeze accounts for 3% to 8% of the total weight of the cement and admixtures. Part of the water is mixed with the antifreeze, and after the remaining water is mixed with the cement and admixtures, a mixture of part of the water and the antifreeze is added thereto and mixed evenly to obtain a grouting material.
[0045] The grouting material is poured into the sleeve to complete the grouting.
[0046] In some embodiments of the present invention, the following steps are preferably included:
[0047] Take 90-120 parts of sand and 80-100 parts of stone and add them to the mixture of cement, admixture and remaining water and mix well;
[0048] Take 0.1-1.6 parts of plastic expansion agent, 7-8.4 parts of calcium oxide expansion agent, 1-5 parts of water reducer, 0.1-1 part of defoamer, xanthan gum and / or sepiolite, add them to part of water and antifreeze and mix them, then add them to the mixture of cement, admixture, sand, stone and remaining water and mix them to obtain the grouting material, wherein the amount of xanthan gum and / or sepiolite accounts for 0.05% to 0.2% of the total weight of the cement and admixture.
[0049] In the present invention, the ambient temperature of the sleeve grouting is obtained to determine the amount of antifreeze, and in the configuration of the grouting material, each component is accurately weighed according to the weight portion, and the amount of antifreeze is adjusted according to the ambient temperature; the requirements of prefabricated buildings for steel bar connections in cold weather can be met, and the invention has broad application prospects.
[0050] In some embodiments of the present invention, the following steps are preferably included:
[0051] Alkaliphilic Bacillus spores and calcium lactate are mixed in a mass ratio of 2:1-5 under vacuum conditions to obtain a capsule core material, the capsule core material is crushed into micrometers, magnesium phosphate cement is used as a capsule wall, the capsule wall material is wrapped around the micrometer-sized capsule core material, and the self-healing microcapsules are obtained by drying the pellets;
[0052] Take 6 to 9 parts of the self-repairing microcapsules, add them into the grouting material and mix them evenly, and then pour them into the sleeve.
[0053] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the following embodiments are provided for further explanation:
[0054] Example 1
[0055] A sleeve grouting material for steel bar connection, comprising the following components in parts by weight:
[0056] 200 parts of silicate cement, 90 parts of admixture, 90 parts of machine-made sand with a fineness modulus of 0.7-1.5, 80 parts of 5-20 mm continuously graded crushed stone, 1 part of antifreeze agent and polycarboxylic acid water reducer, 0.1 part of ether defoamer or silicone defoamer, 0.1 part of plastic expansion agent, 7 parts of calcium oxide expansion agent, xanthan gum, 160 parts of water, wherein the amount of xanthan gum accounts for 0.05% of the total weight of the cement and admixture, wherein the antifreeze agent comprises a silicate antifreeze agent and a polycarboxylic acid antifreeze agent in a mass ratio of 10:1.
[0057] The sleeve grouting method based on the sleeve grouting material for steel bar connection comprises:
[0058] 1) The ambient temperature of the sleeve grouting is 0° C., the amount of antifreeze used is 0.8% of the total weight of the cement and admixtures, and the antifreeze is added to part of the water;
[0059] 2) Insert the steel bar into the prefabricated sleeve;
[0060] 3) Take cement, admixtures, machine-made sand with a fineness modulus of 0.7 to 1.5, and 5 to 20 mm continuously graded gravel, add them into the remaining water and mix well;
[0061] 4) adding a polycarboxylic acid water-reducing agent, an ether defoaming agent or a silicone defoaming agent, a plastic expansion agent, a calcium oxide expansion agent, xanthan gum and / or sepiolite to the mixture of the antifreeze agent and part of the water in step 1) and mixing well, then adding the mixed mixture to the mixture in step 3) and mixing well to obtain a grouting material.
[0062] 5) Pour the grouting material into the sleeve to complete the grouting.
[0063] Example 2
[0064] A sleeve grouting material for steel bar connection, comprising the following components in parts by weight:
[0065] 250 parts of silicate cement, 180 parts of admixture, 105 parts of machine-made sand with a fineness modulus of 0.7-1.5, 90 parts of 5-20 mm continuously graded crushed stone, 3 parts of antifreeze agent, polycarboxylic acid water reducer, 0.55 parts of ether defoamer or silicone defoamer, 0.85 parts of plastic expansion agent, 7.7 parts of calcium oxide expansion agent, sepiolite, and 167.5 parts of water, wherein the amount of xanthan gum and / or sepiolite accounts for 0.12% of the total weight of the cement and admixture, wherein the antifreeze agent comprises a silicate antifreeze agent and a polycarboxylic acid antifreeze agent in a mass ratio of 10:1.
[0066] The sleeve grouting method based on the sleeve grouting material for steel bar connection comprises:
[0067] 1) The ambient temperature of the sleeve grouting is -4°C, the amount of antifreeze used is 1.8% of the total weight of the cement and admixtures, and the antifreeze is added to part of the water;
[0068] 2) Insert the steel bar into the prefabricated sleeve;
[0069] 3) Take cement, admixtures, machine-made sand with a fineness modulus of 0.7 to 1.5, and 5 to 20 mm continuously graded gravel, add them into the remaining water and mix well;
[0070] 4) adding a polycarboxylic acid water-reducing agent, an ether defoaming agent or a silicone defoaming agent, a plastic expansion agent, a calcium oxide expansion agent, xanthan gum and / or sepiolite to the mixture of the antifreeze agent and part of the water in step 1) and mixing well, then adding the mixed mixture to the mixture in step 3) and mixing well to obtain a grouting material.
[0071] 5) Pour the grouting material into the sleeve to complete the grouting.
[0072] Example 3
[0073] A sleeve grouting material for steel bar connection, comprising the following components in parts by weight:
[0074] 300 parts of Portland cement, 270 parts of admixture, 120 parts of machine-made sand with a fineness modulus of 0.7-1.5, 100 parts of 5-20 mm continuously graded crushed stone, 5 parts of antifreeze agent and polycarboxylic acid water reducer, 1 part of ether defoamer or silicone defoamer, 1.6 parts of plastic expansion agent, 8.4 parts of calcium oxide expansion agent, xanthan gum and sepiolite in a mass ratio of 1:1, and 175 parts of water, wherein the amount of xanthan gum and sepiolite accounts for 0.2% of the total weight of the cement and admixture, wherein the antifreeze agent comprises a silicate antifreeze agent and a polycarboxylic acid antifreeze agent in a mass ratio of 10:1.
[0075] The sleeve grouting method based on the sleeve grouting material for steel bar connection comprises:
[0076] 1) The ambient temperature of the sleeve grouting is -10°C, the amount of antifreeze used is 3% of the total weight of the cement and admixtures, and the antifreeze is added to part of the water;
[0077] 2) Insert the steel bar into the prefabricated sleeve;
[0078] 3) Take cement, admixtures, machine-made sand with a fineness modulus of 0.7 to 1.5, and 5 to 20 mm continuously graded gravel, add them into the remaining water and mix well;
[0079] 4) adding a polycarboxylic acid water-reducing agent, an ether defoaming agent or a silicone defoaming agent, a plastic expansion agent, a calcium oxide expansion agent, xanthan gum and / or sepiolite to the mixture of the antifreeze agent and part of the water in step 1) and mixing well, then adding the mixed mixture to the mixture in step 3) and mixing well to obtain a grouting material.
[0080] 5) Pour the grouting material into the sleeve to complete the grouting.
[0081] Example 4
[0082] A sleeve grouting material for steel bar connection, comprising the following components in parts by weight:
[0083] 210 parts of silicate cement, 100 parts of admixture, 100 parts of machine-made sand with a fineness modulus of 0.7 to 1.5, 85 parts of 5 to 20 mm continuous graded crushed stone, 2 parts of antifreeze agent and polycarboxylate water reducer, 0.2 parts of ether defoamer or silicone defoamer, 0.4 parts of plastic expansion agent, 7.3 parts of calcium oxide expansion agent, xanthan gum, 6 parts of self-repairing microcapsules, 161 parts of water, the amount of xanthan gum accounts for 0.08% of the total weight of the cement and admixture, wherein the antifreeze agent includes silicate antifreeze agent and polycarboxylate antifreeze agent in a mass ratio of 10:1. The capsule core of the self-repairing microcapsule includes alkaliphilic bacillus spores and calcium lactate in a mass ratio of 2:1, the capsule wall of the self-repairing microcapsule is magnesium phosphate cement, and the mass ratio of the capsule wall to the capsule core is 2:1. The preparation method of the self-repairing microcapsule comprises: mixing alkaliphilic bacillus spores with calcium lactate under vacuum conditions to obtain a capsule core material, crushing the capsule core material into micrometers, using magnesium phosphate cement as a capsule wall, wrapping the capsule wall material outside the micrometer-sized capsule core material, and drying to obtain a self-repairing microcapsule. 2% of nano calcium carbonate is added to the admixture, and the rest is zeolite powder.
[0084] The sleeve grouting method based on the sleeve grouting material for steel bar connection comprises:
[0085] 1) The ambient temperature of the sleeve grouting is -2°C, the amount of antifreeze used is 1.4% of the total weight of the cement and admixtures, and the antifreeze is added to part of the water;
[0086] 2) Insert the steel bar into the prefabricated sleeve;
[0087] 3) Take cement, admixtures, machine-made sand with a fineness modulus of 0.7 to 1.5, and 5 to 20 mm continuously graded gravel, add them into the remaining water and mix well;
[0088] 4) adding a polycarboxylic acid water reducer, an ether defoamer or a silicone defoamer, a plastic expansion agent, a calcium oxide expansion agent, xanthan gum and / or sepiolite to the mixture of the antifreeze agent and part of the water in step 1) and mixing, then adding the mixed mixture to the mixture in step 3) and mixing, and finally adding the prepared self-repairing microcapsules to the above mixture and mixing to obtain a grouting material.
[0089] 5) Pour the grouting material into the sleeve to complete the grouting.
[0090] Example 5
[0091] A sleeve grouting material for steel bar connection, comprising the following components in parts by weight:
[0092] 220 parts of silicate cement, 120 parts of admixtures, 110 parts of machine-made sand with a fineness modulus of 0.7 to 1.5, 90 parts of 5 to 20 mm continuous graded crushed stone, 4 parts of antifreeze agent and polycarboxylate water reducer, 0.6 parts of ether defoamer or silicone defoamer, 0.9 parts of plastic expansion agent, 7.6 parts of calcium oxide expansion agent, sepiolite, 7.5 parts of self-repairing microcapsules, 170 parts of water, the amount of sepiolite accounts for 0.1% of the total weight of the cement and admixtures, wherein the antifreeze agent includes silicate antifreeze agent and polycarboxylate antifreeze agent in a mass ratio of 10:1. The capsule core of the self-repairing microcapsule includes alkaliphilic bacillus spores and calcium lactate in a mass ratio of 2:3, the capsule wall of the self-repairing microcapsule is magnesium phosphate cement, and the mass ratio of the capsule wall to the capsule core is 6:1. The preparation method of the self-repairing microcapsule comprises: mixing alkaliphilic bacillus spores with calcium lactate under vacuum conditions to obtain a capsule core material, crushing the capsule core material into micron-sized particles, using magnesium phosphate cement as a capsule wall, wrapping the capsule wall material outside the micron-sized capsule core material, and drying the resulting self-repairing microcapsule. The admixture is one or more of bentonite, zeolite powder, fly ash or silica fume, and 2.5% of nano calcium carbonate is added to the admixture, and the rest is bentonite and fly ash in a mass ratio of 1:1.
[0093] The sleeve grouting method based on the sleeve grouting material for steel bar connection comprises:
[0094] 1) The ambient temperature of the sleeve grouting is -8°C, the amount of antifreeze used is 2.4% of the total weight of the cement and admixtures, and the antifreeze is added to part of the water;
[0095] 2) Insert the steel bar into the prefabricated sleeve;
[0096] 3) Take cement, admixtures, machine-made sand with a fineness modulus of 0.7 to 1.5, and 5 to 20 mm continuously graded gravel, add them into the remaining water and mix well;
[0097] 4) adding a polycarboxylic acid water reducer, an ether defoamer or a silicone defoamer, a plastic expansion agent, a calcium oxide expansion agent, xanthan gum and / or sepiolite to the mixture of the antifreeze agent and part of the water in step 1) and mixing, then adding the mixed mixture to the mixture in step 3) and mixing, and finally adding the prepared self-repairing microcapsules to the above mixture and mixing to obtain a grouting material.
[0098] 5) Pour the grouting material into the sleeve to complete the grouting.
[0099] Example 6
[0100] A sleeve grouting material for steel bar connection, comprising the following components in parts by weight:
[0101] 280 parts of silicate cement, 260 parts of admixture, 110 parts of machine-made sand with a fineness modulus of 0.7 to 1.5, 95 parts of 5 to 20 mm continuous graded crushed stone, 1 to 5 parts of antifreeze agent and polycarboxylate water reducer, 0.9 parts of ether defoamer or silicone defoamer, 1.5 parts of plastic expansion agent, 8.2 parts of calcium oxide expansion agent, xanthan gum, 9 parts of self-repairing microcapsules, 172 parts of water, the amount of xanthan gum accounts for 0.18% of the total weight of the cement and admixture, wherein the antifreeze agent includes silicate antifreeze agent and polycarboxylate antifreeze agent in a mass ratio of 10:1. The capsule core of the self-repairing microcapsule includes alkaliphilic bacillus spores and calcium lactate in a mass ratio of 2:5, the capsule wall of the self-repairing microcapsule is magnesium phosphate cement, and the mass ratio of the capsule wall to the capsule core is 10:1. The preparation method of the self-repairing microcapsule includes: mixing alkaliphilic bacillus spores with calcium lactate under vacuum conditions to obtain a capsule core material, crushing the capsule core material into micrometers, using magnesium phosphate cement as a capsule wall, wrapping the capsule wall material outside the micrometer-sized capsule core material, and drying to obtain a self-repairing microcapsule. 5% of nano calcium carbonate is added to the admixture, and the remaining components are silica fume and fly ash in a mass ratio of 1:1.
[0102] The sleeve grouting method based on the sleeve grouting material for steel bar connection comprises:
[0103] 1) The ambient temperature of the sleeve grouting is -15°C, the amount of antifreeze used is 8% of the total weight of the cement and admixtures, and the antifreeze is added to part of the water;
[0104] 2) Insert the steel bar into the prefabricated sleeve;
[0105] 3) Take cement, admixtures, machine-made sand with a fineness modulus of 0.7 to 1.5, and 5 to 20 mm continuously graded gravel, add them into the remaining water and mix well;
[0106] 4) adding a polycarboxylic acid water reducer, an ether defoamer or a silicone defoamer, a plastic expansion agent, a calcium oxide expansion agent, xanthan gum and / or sepiolite to the mixture of the antifreeze agent and part of the water in step 1) and mixing, then adding the mixed mixture to the mixture in step 3) and mixing, and finally adding the prepared self-repairing microcapsules to the above mixture and mixing to obtain a grouting material.
[0107] 5) Pour the grouting material into the sleeve to complete the grouting.
[0108] Effect verification
[0109] The properties of the grouting materials prepared in Examples 1-6 were measured respectively. The compressive strengths of the grouting materials prepared in Examples 1-6 at 28 days were 109.7, 114.3, 111.0, 112.6, 118.5 and 114.7 MPa respectively, and there were no obvious defects on the surfaces.
[0110] After grouting of the grouting material prepared in Examples 4, 5 and 6 is completed, the formed specimens are standardly cured for 7 days, and then cracks are made using a universal testing machine. The width of the cracks is adjusted to 5 mm and divided into three groups. Each group of specimens is then placed at ambient temperatures of 5°C, 10°C and 15°C for curing, respectively. The self-repair of the cracks is observed at 0 and 28 days of curing, and it is found that the test blocks of Examples 4, 5 and 6 are completely repaired at 57 days, 56 days and 57 days, respectively, at an ambient temperature of 5°C, at 45 days, 44 days and 45 days, respectively, at an ambient temperature of 10°C, and at 34 days, 32 days and 33 days, respectively, at an ambient temperature of 15°C.
[0111] As described above, the grouting material of the present invention has excellent cold-proof effect, and can well complete the connection of steel sleeves even in cold climates. At the same time, the components of the grouting material added with self-repairing microcapsules can repair cracks when the ambient temperature reaches above 5°C, thereby improving the durability of the grouting material.
[0112] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.
Claims
1. A sleeve grouting material for steel bar connection, characterized in that: The composition comprises the following components in parts by weight: 200-300 parts of cement, 90-270 parts of admixture, and 160-175 parts of antifreeze and water, wherein the antifreeze comprises a silicate antifreeze and a polycarboxylic acid antifreeze in a mass ratio of 10:1, wherein when used at a temperature of 0 to -4°C, the amount of the antifreeze accounts for 0.8% to 2% of the total weight of the cement and the admixture; when used at a temperature of -4 to -10°C, the amount of the antifreeze accounts for 1.8% to 3% of the total weight of the cement and the admixture; when used at a temperature below -10°C, the amount of the antifreeze accounts for 3% to 8% of the total weight of the cement and the admixture.
2. The sleeve grouting material for connecting steel bars according to claim 1, characterized in that: The invention also comprises the following components in parts by weight: 90 to 120 parts of sand and 80 to 100 parts of stone.
3. The sleeve grouting material for connecting steel bars according to claim 1, characterized in that: The invention also comprises the following components in parts by weight: 1 to 5 parts of a water reducing agent and 0.1 to 1 part of a defoaming agent.
4. The sleeve grouting material for connecting steel bars according to claim 1, characterized in that: The cement and admixture also include the following components in parts by weight: xanthan gum and / or sepiolite, wherein the amount of the xanthan gum and / or sepiolite accounts for 0.05% to 0.2% of the total weight of the cement and the admixture.
5. The sleeve grouting material for connecting steel bars according to claim 1, characterized in that: The invention also comprises the following components in parts by weight: 0.1 to 1.6 parts of plastic expansion agent and 7 to 8.4 parts of calcium oxide expansion agent.
6. The sleeve grouting material for connecting steel bars according to claim 1, characterized in that: It also includes the following components in parts by weight: 6 to 9 parts of self-repairing microcapsules, wherein the core of the self-repairing microcapsules includes alkaliphilic Bacillus spores and calcium lactate in a mass ratio of 2:1 to 5, the capsule wall of the self-repairing microcapsule is magnesium phosphate cement, and the mass ratio of the capsule wall to the capsule core is 2 to 10:
1.
7. A sleeve grouting method based on the sleeve grouting material for steel bar connection according to claim 1, characterized in that: The steps include: Get the sleeve grouting environment temperature; Inserting the steel bars into the prefabricated sleeves; According to weight proportions, 200-300 parts of cement, 90-270 parts of admixtures, and 160-175 parts of antifreeze and water are taken. Antifreeze is taken according to the ambient temperature of sleeve grouting. The antifreeze includes silicate antifreeze and polycarboxylic acid antifreeze in a mass ratio of 10:
1. When used at a temperature of 0 to -4°C, the amount of the antifreeze accounts for 0.8% to 2% of the total weight of the cement and admixtures. When used at a temperature of -4 to -10°C, the amount of the antifreeze accounts for 1.8% to 3% of the total weight of the cement and admixtures. When used at a temperature below -10°C, the amount of the antifreeze accounts for 3% to 8% of the total weight of the cement and admixtures. Part of the water is mixed with the antifreeze, and after the remaining water is mixed with the cement and admixtures, a mixture of part of the water and the antifreeze is added thereto and mixed evenly to obtain a grouting material. The grouting material is poured into the sleeve to complete the grouting.
8. The sleeve grouting method according to claim 7, characterized in that: The following steps are also included: Take 90-120 parts of sand and 80-100 parts of stone and add them to the mixture of cement, admixture and remaining water and mix well; Take 0.1-1.6 parts of plastic expansion agent, 7-8.4 parts of calcium oxide expansion agent, 1-5 parts of water reducer, 0.1-1 part of defoamer, xanthan gum and / or sepiolite, add them to part of water and antifreeze and mix them, then add them to the mixture of cement, admixture, sand, stone and remaining water and mix them to obtain the grouting material, wherein the amount of xanthan gum and / or sepiolite accounts for 0.05% to 0.2% of the total weight of the cement and admixture.
9. The sleeve grouting method according to claim 7, characterized in that: The following steps are also included: Alkaliphilic Bacillus spores and calcium lactate are mixed in a mass ratio of 2:1-5 under vacuum conditions to obtain a capsule core material, the capsule core material is crushed into micrometers, magnesium phosphate cement is used as a capsule wall, the capsule wall material is wrapped around the micrometer-sized capsule core material, and the self-healing microcapsules are obtained by drying the pellets; Take 6 to 9 parts of the self-repairing microcapsules, add them into the grouting material and mix them evenly, and then pour them into the sleeve.